THE ROLE OF THE POPULATION HEALTH SYSTEM IN THE DEVELOPMENT OF URBANIZATION PROCESSES IN THE SURKHANDARDYA AND KASHKADARYA REGIONS IN THE EARLY YEARS OF INDEPENDENCE - Tursunov Anvar Saypullayevich (American Journals Publishing, 2025)
The article analyzes the development of urbanization processes and the healthcare system in Surkhandarya and Kashkadarya regions during the early years of independence. The study examines the growth of medical services in cities, the establishment of new polyclinics and departments, the introduction of paid medical services, measures to combat epidemiological situations and infectious diseases, as well as the formation of health improvement and sanatorium systems. Additionally, it analyzes the economic and social conditions, intercity and interregional medical infrastructure, international relations, and state policy in maintaining public health.
Keywords: Urbanization, public health, medical services, paid services, epidemiology, sanatorium system, Surkhandarya region, Kashkadarya region.